Implikasi Putusan Mahkamah Konstitusi Nomor 60/PUU-XXII/2024 terhadap Demokratisasi Pemilihan Kepala Daerah - Muhammad Anwar Soleh; Durohim Amnan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study will discuss how the implications of the MK 60/PUU-XXII/2024 decision on the 2024 simultaneous regional election contestation and how the idealita (ideal concept) threshold for the nomination of regional heads in the election system in Indonesia. This study also aims to address the issue of the threshold of the nomination, both the nomination of the president and the nomination of regional heads which from time to time always cause problems and difficult to find a middle point. Type of research used normative-juridical approach to legislation and cases as well as research used library (library research) with secondary data. The results of the discussion are the result of this decision, namely the potential of each political party to propose a candidate for Regional Head is increasingly wide open and the competition is believed to be increasingly competitive which can produce a skilled and qualified leader because it has gone through a rigorous competition process from each candidate proposed by a political party. This implication is a space that has been awaited by political parties and the community because the more candidates for regional heads, the more choices that can be investigated by the community.